Avaliação do comportamento alimentar e da suscetibilidade para transtornos alimentares em candidatos à cirurgia bariátrica atendidos em um hospital público de referência em Belém-Pa. - VASCONCELOS, Jairisson Augusto Santa Brígida (2023)
Introduction: Current studies have evidenced the presence of changes in eating behavior, in addition to vulnerability to eating disorders in candidates for bariatric surgery, which may be related to possible post-surgical failure. Objective: To analyze characteristics of eating behavior and factors associated with susceptibility to eating disorders in candidates for bariatric surgery. Methodology: This is a descriptive-analytical cross-sectional study, with individuals who are candidates for bariatric surgery followed up in a public hospital in Belém. A questionnaire with sociodemographic, clinical and physical activity data, the Three Food Factors Questionnaire (TFEQ-R21) instrument was used to investigate eating behavior and the Disordered Eating Attitudes Scale (DEAS) to assess susceptibility to eating disorders. Weight and height were measured using a platform scale to assess nutritional status. Data were analyzed using SPSS software, v.24 (statistical significance p<0.05). Results: A total of 75 participants were evaluated, 92% (n=69) were women and the mean age was 34.9±9,2 years. As for the analysis of the TFEQ-R21, the domain with the highest score was the food restriction domain, with a mean of 55.2±19.7, followed by the lack of food control, which was 39.4 ±20.6 and the eating domain which was 37.7±26.2 (p<0.001). Regarding the DEAS score, the mean was 2.1±0.7 and regarding its classification, 13.6% (n=10) fit without disordered eating attitudes and 86.7% (n=65) with disordered eating attitudes (p<0.001). In the bivariate correlation analyses, a significant negative correlation was found between BMI and the emotional eating domain (r²= - 0.219; p=0.030) and the domain of uncontrolled eating (r²= -0.231, p=0.023), in relation to the DEAS score, there was a significant positive correlation with the domain of food restriction (r²=0.192; p=0.049). Participants who practiced physical activity in the last 3 months had higher scores in the food restriction domain (p<0.001) and lower scores in the emotional eating domain (p=0.008). Participants who used weight-loss drugs in the last 3 months had a lower score for disordered eating attitudes (p=0.003). Conclusion: The importance of the multidisciplinary team throughout the preoperative period to identify dysfunctional eating patterns and early intervention is highlighted.